Nautical Tourism - Lukovic, Tihomir (CABI, 2014)
In this time of global economic crisis and the accompanying stagnation of ideas and of new visions in economic development and progress, nautical tourism is an industry that is developing at a continuous rate. To my knowledge, there is no widely recognized book in English that aims to demystify the concept of nautical tourism, analyse its industries and explain its development and potentials. Therefore it is natural to conclude that science has not been sufficiently engaged in the issue, that there is little research dealing with nautical tourism, especially at universities, and even fewer experts have been engaged in the phenomenon of nautical tourism. At the same time, all basic and accompanying industries of nautical tourism continue to achieve good economic results. Without relying on any particular expertise in the field, investors have recognized its potentials for development and profit and it is developing in all world markets regardless of the global economic crisis. However, it is clear that due to a lack of specific knowledge of its current state and nature the nautical tourism industry has not yet achieved its full potential. It is entirely reasonable to anticipate that this situation will improve. The development of nautical tourism is related to the level of general economic develop- ment and the best results have so far been achieved in the European and the Pacific markets. However, this is a time of new world markets that, for political reasons, have not yet been opened: these are rapidly opening and expanding. Nautical tourism is a development oppor- tunity for all world markets, although a headline from an American journal should be borne in mind: ‘Do as we say, not as we do’. 1 The important implication is that every market and local economy, while drawing lessons from the European and Pacific experience, should find its own appropriate model for the development of nautical tourism if it hopes to succeed on a global scale. Since nautical tourism is a large and complex industry with specific features in each mega- and micro-market, I have managed to engage leading experts in nautical tourism with the aim of analysing and publishing the results of our research that have followed from decades of hard work and studies in nautical tourism. Our results, which each of us have achieved indi- vidually, are valuable and therefore should be made public so as to become an effective basis for future research. We are aware that the primary function of this book is as a stimulus to future cooperation between all researchers, scientists and specialists with relevant expertise. This book should therefore be seen as a ‘first edition’, since we are planning future editions that will have new co-authors and contain new information and results.